The Prognostic Potential of Neurokinin 1 Receptor in Breast Cancer and Its Relationship with Ki-67 Index - Maha S. Al-Keilani; Rana Elstaty; Mohammad A. Alqudah (International Journal of Breast Cancer, 2022)
Background. Neurokinin 1 receptor (NK1R) is a promising biomarker and therapeutic target in breast cancer. This study was aimed at investigating the expression level of NK1R in breast cancer tissues and its relationship with proliferation index as measured by Ki-67, clinicopathological characteristics of patients, and overall survival rate. Methods. Immunohistochemical expression of NK1R and Ki-67 was measured in 164 paraffin-embedded breast cancer tissues of four molecular subtypes (42 HER2-enriched, 40 luminal A, 42 luminal B, and 40 triple negative). NK1R was scored semiquantitatively, while Ki-67 was obtained by the percentage of total number of tumor cells with nuclear staining. The optimal cutoff values for NK1R and Ki-67 were assessed by Cutoff Finder. Pearson’s Chi-square (χ2) and Fisher’s exact tests were used to compare the staining scores between groups. The Kaplan-Meier method with log-rank test was used for survival analysis. ANOVA and Student’s t-test were used to compare group means. Results. A total of 164 patients were included in the study which represented females with invasive ductal carcinoma. NK1R was expressed at high levels in about 34% of investigated cases. The mean Ki-67 level was about 27% and 41.5% of sample had high Ki-67 (expression level>22%). NK1R expression levels were associated with higher tumor grade (p=0.021) and high Ki-67 (p=0.012). NK1R expression negatively impacted overall survival in grade II tumors (p=0.027). Conclusion. NK1R contributes to cellular proliferation and is associated with negative prognosis in breast cancer. These findings suggest the potential role of NK1R as a therapeutic target in breast cancer.